The effect of obesity on postural stability during a standardized lifting task. Issue 3 (4th March 2017) - Pajoutan, Mojdeh; Xu, Xu; Cavuoto, Lora A.
ABSTRACT: The objective of this study was to assess the effect of obesity on postural stability during a standardized lifting task. Twelve young males, six obese and six non-obese, completed three replications of repeated six lifts (at a rate of six lifts per minutes) at two levels of loads (10% and 25% of capacity) crossed with two levels of orientation (0° and 45° from sagittal plane). Postural stability measures showed that center of pressure sway path and sway area were ∼21% and ∼53% lower with obesity, respectively. Additionally, frequency band of amplitude spectrum in the medial lateral direction at 0° lifting orientation was significantly lower with obesity. The results suggest that obesity, as measured by body mass index, does not impair balance control in healthy young males when lifting load is relative to the capacity.